Fundamentalisme agama sebagai prediktor intoleransi politik pemuda Hindu di Bali - Marvel M.A.A.N Sihombing; Tutut Chusniyah; Pravissi Shanti (Flourishing Journal, 2021)
Abstract: This study aims to (1) determine the level of religious fundamentalism of Hindu youth in Bali, (2) to determine the level of political intolerance of Hindu youth in Bali, (3) to determine religious fundamentalism as a predictor of political intolerance of Hindu youth in Bali. This research is quantitative research with descriptive and correlational predictive methods. The population in this study were Hindu youth in Bali and the sample used in this study was 90 people with a purposive sampling technique. The instrument in this research is a scale of religious fundamentalism and a scale of political intolerance. The analysis of the research data uses descriptive analysis with categorization based on the T value. Hypothesis testing uses simple linear regression analysis techniques. The results of this study indicate that Hindu youth in Bali (1) have religious fundamentalism which is categorized as high, (2) have political tolerance, and (3) religious fundamentalism is not a predictor of political intolerance because of the significance level of 0.644. Keywords: Religious Fundamentalism; Political Intolerance; Hindu Youth Abstrak: Penelitian ini bertujuan untuk mengetahui (1) tingkat fundamentalisme agama pemuda Hindu di Bali, (2) tingkat intoleransi politik pemuda Hindu di Bali, (3) mengetahui fundamentalisme agama sebagai prediktor intoleransi politik pemuda Hindu di Bali. Penelitian ini merupakan penelitian kuantitatif dengan metode deskriptif dan korelasional prediktif. Populasi dalam penelitian ini yaitu pemuda Hindu di Bali dan sampel yang digunakan dalam penelitian ini sebanyak 90 orang dan menggunakan teknik purposive sampling. Alat ukur dalam penelitian ini berupa skala fundamentalisme agama dan skala intoleransi politik.Analisis data penelitian menggunakan analisis deskriptif dengan pengkategorian berdasarkan pada nilai T. Uji hipotesis menggunakan teknik analisis regresi linier sederhana. Hasil penelitian menunjukkan bahwa pemuda Hindu di Bali (1) memiliki fundamentalisme agama yang dikategorikan tinggi, (2) memiliki toleransi politik , dan (3) fundamentalisme agama bukan merupakan prediktor intoleransi politik karena taraf signifikansi 0,644. Kata kunci: Fundamentalisme Agama; Intoleransi Politik; Pemuda Hindu